(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: Taxation was and still is one of the main resources on which the state relies for its public expenditures. However, this resource is taking a retreat from performing its desired role, we find the percentage of the contribution of taxes in financing public expenditures does not represent only a weak percentage of its dependence entirely on oil revenues, so the tax system in Iraq suffers from its shortcomings in achieving the financing of public expenditures, so the percentage of revenues of the General Tax Authority is estimated at (1.14-6.11%) of the total revenues, which negatively affected the tax system in Iraq, The research was based on the main hypothesis that the measurement and analysis of tax effort is a role in maximizing tax revenue, and the researcher reached several conclusions, most notably the index of tax effort to the low efficiency of the tax system in Iraq, as the tax system could not exploit the tax energy efficiently, and this led to the loss of tax revenues that would have provided tax revenue that feeds government expenditures, and tax rates require the need to replace some of the applied taxes with more effective taxes that contribute to increasing tax revenues and feeding the public budget. The most prominent recommendations of the research were due to the decrease in tax effort during the research period with a greater tax capacity, the tax policy should go towards new paths, to expand the taxable incomes and raise their percentage, by activating their role in achieving financial, economic and social goals, and thus reducing the dependence of the state budget on the oil sector, in a way that makes the economy more stable and less affected by external shocks.